Extracting adverse drug events from clinical notes: a systematic review of approaches used - Modi, Salisu; Kasmiran, Khairul Azhar; Mohd Sharef, Nurfadhlina; Sharum, Mohd Yunus (Academic Press, 2024)
Background: An adverse drug event (ADE) is any unfavorable effect that occurs due to the use of a drug. Extracting ADEs from unstructured clinical notes is essential to biomedical text extraction research because it helps with pharmacovigilance and patient medication studies.